Novel Synthesis Route for Chitosan-Coated Zinc Ferrite Nanoparticles as Potential Sorbents for Wastewater Treatment. Issue 12 (1st December 2016) - Ignat, Maria; Samoila, Petrisor; Cojocaru, Corneliu; Sacarescu, Liviu; Harabagiu, Valeria
Abstract : Magnetic chitosan–zinc ferrite (ChZnF) composites were proposed as potential adsorbents due to their appropriate physical characteristics and facile separation under external magnetic fields. The magnetic component (ZnFe2 O4 ) was prepared by the sol–gel autocombustion method that yields nanometric spinel compounds with narrow size distribution and with low energy consumption. A certain amount of magnetic powder was dispersed consecutively by ultrasonication in a chitosan-PEG (polyethylene glycol) mixture, in order to obtain the desired nanocomposite. The as-obtained materials were characterized by FT-IR (Fourier transform infrared spectroscopy), XRD (X-ray diffraction), TEM (transmission electron microscopy), small-angle X-ray scattering, and Brunauer–Emmett–Teller test measurements. Finally, the chitosan-ferrite nanomaterial was successfully tested in simulated wastewater treatments. Different kinetic and equilibrium models have been fitted by nonlinear regression to analyze the adsorption data.